High-nickel lithium-rich manganese-based all-solid-state battery positive electrode material and preparation method thereof
By covering the NiO layer on the surface of the core of nickel-cobalt manganese oxide, the problem of oxygen generated by lithium-rich manganese-based positive electrode material during the lattice oxygen redox process is solved, and the specific capacity and cycle stability of the material are improved.
Patent Information
- Application Number
- CN202411697832.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Lithium-rich manganese-based positive electrode material produces oxygen during the lattice oxygen redox process, resulting in structural transformation, low initial battery Coulomb efficiency, voltage decay and hysteresis.
By coating the NiO layer on the inner core surface of the nickel-cobalt manganate, a high-nickel lithium-rich manganese-based all-solid-state battery positive electrode material is formed, and the weight percentage of the NiO layer is 1 to 5%.
The chemical stability of the NiO layer acts as a protective layer at the positive electrode/electrolyte interface, stabilizes the lattice oxygen on the surface of the positive electrode material, reduces phase degradation, and acts as a buffer layer to limit the side reaction between the positive electrode material and the solid electrolyte, improving the specific capacity and cyclic stability of the material.
Smart Images

Figure CN119674052A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion battery materials, and in particular to a high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material and a preparation method thereof. Background Art
[0002] All-solid-state batteries have significantly higher energy density and safety performance than liquid batteries and have excellent commercial prospects. The positive electrode, negative electrode and electrolyte are the key components of the battery. Over the past few decades, many breakthroughs have been made in the negative electrode and electrolyte. The positive electrode material has become an important factor limiting the performance improvement of lithium batteries, accounting for about 30-40% of the cost of lithium-ion batteries. Compared with current positive electrode materials, lithium-rich manganese-based positive electrode materials have the advantages of higher discharge specific capacity (>250mAh / g) and low cost, and are expected to become the next generation of lithium-ion battery positive electrode materials.
[0003] Lithium-rich manganese-based cathode materials have a special "Li-O-Li" structure, which can undergo lattice oxygen redox reactions at high voltages, thereby obtaining high specific capacity. However, during the lattice oxygen redox process, part of the oxygen will be irreversibly oxidized to oxygen and form oxygen vacancies, resulting in a decrease in the migration energy of transition metal ions to the vacancies in the lithium layer, thereby inducing structural transformation, and ultimately causing problems such as low initial coulombic efficiency, voltage decay, and hysteresis of the battery. On the other hand, the generated oxygen attacks the electrolyte, forming a large number of byproducts at the cathode / electrolyte interface, hindering the interfacial lithium ion transmission and deteriorating the cycle performance and rate performance of lithium-rich manganese-based cathode materials.
[0004] At present, the performance optimization methods for lithium-rich manganese-based cathode materials include coating, doping, electrode structure design, etc., with the aim of solving the inherent problems of oxygen precipitation and slow electron / ion transport in lithium-rich manganese-based cathode materials. For example, Zhang Qiang et al. introduced stable polyanion SO on the surface of lithium-rich manganese-based cathode materials. 3 2- Substitute lattice oxygen O 2- , stabilize the cathode / electrolyte interface, inhibit the release of oxygen to a certain extent, and significantly improve the initial charge and discharge efficiency and cycle performance of lithium-rich manganese-based materials. Pan Hongge and others increased the electronic and ionic conductivity of the material by 4 orders of magnitude by adjusting the ratio of Ni and Co in the lithium-rich manganese-based material, and obtained ultra-high discharge specific capacity and stability for 1000 cycles. However, these methods are relatively complicated and difficult to achieve large-scale production and application. Therefore, it is necessary to develop a simpler and more effective method to improve the structural stability of lithium-rich manganese-based cathode materials and the electrochemical performance of solid-state batteries. Summary of the invention
[0005] The purpose of the present application is to overcome the deficiencies of the above-mentioned prior art and to provide a high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material and a preparation method thereof.
[0006] To achieve the above-mentioned purpose, the technical solution adopted in this application is: a high-nickel lithium-rich manganese-based all-solid-state battery positive electrode material, comprising a nickel-cobalt-manganese oxide lithium core and a NiO layer coated on the surface of the core;
[0007] The chemical formula of the lithium nickel cobalt manganese oxide core is shown in formula (I):
[0008] aLi 2 MnO 3 ·(1-a)LiMn 1 / 3 Ni 1 / 3 Co 1 / 3 O 2 (I)
[0009] Where 0.4<a<0.6;
[0010] In the high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material, the weight percentage of NiO is 1-5%.
[0011] The high-nickel-rich lithium-manganese-based all-solid-state battery positive electrode material of the present invention is coated with a NiO layer on the surface of the nickel-cobalt-manganese-oxide lithium core, and when the weight percentage of NiO in the positive electrode material is 1-5% (such as 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% and 5%, etc., but not limited to the above content), the specific capacity and cycle stability of the material can be improved. The inventor speculates that it may be due to the chemical stability of the surface NiO coating layer that it acts as a protective layer at the positive electrode / electrolyte interface. On the one hand, it can stabilize the surface lattice oxygen of the positive electrode material and reduce its phase degradation during the cycle; on the other hand, it can also serve as a buffer layer to limit the direct contact between the positive electrode material and the solid electrolyte, thereby weakening the side reaction between the positive electrode material and the solid electrolyte, and ultimately improving the specific capacity and cycle performance of the solid-state battery.
[0012] The core of the lithium nickel cobalt manganese oxide is a quasi-spherical particle, and the D50 (secondary particle) is 1 to 10 μm (such as 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm and 10 μm, etc., but not limited thereto), and the thickness of the NiO layer is 5 to 20 nm (such as 5 nm, 7 nm, 9 nm, 11 nm, 13 nm, 15 nm, 17 nm, 19 nm and 20 nm, etc., but not limited thereto). The D50 particle size of the core of the lithium nickel cobalt manganese oxide can be obtained by statistical testing with a scanning electron microscope, and the average value is taken after testing the particle size of 50 particles. Preferably, the D50 particle size of the primary particles of the lithium nickel cobalt manganese oxide is 0.1 to 1 μm. The thickness of the NiO layer is obtained by transmission electron microscopy (TEM) testing.
[0013] Preferably, the average particle size of the nickel manganese cobalt lithium oxide core is 3 to 7 μm. The nickel manganese cobalt lithium oxide can be purchased from the market, or can be prepared by existing conventional methods, such as the method mentioned in Jun Wang, Xiayin Yao, Xufeng Zhou and Zhaoping Liu*Synthesis and electrochemical properties of layered lithium transition metal oxides [J] J. Mater. Chem., 2011, 21, 2544-2549.
[0014] Preferably, in the high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material, the weight percentage of NiO is 2-4%. NiO at this content can show better specific capacity and cycle stability.
[0015] The present invention also provides a method for preparing the above-mentioned high-nickel lithium-rich manganese-based all-solid-state battery positive electrode material, comprising the following steps:
[0016] S1. Obtaining lithium nickel cobalt manganese oxide particles;
[0017] S2. Evenly mix the nickel cobalt manganese oxide particles and the nickel salt to obtain a mixture, sinter the mixture to decompose the nickel salt into nickel oxide, and cool the mixture to obtain the high-nickel lithium-rich manganese-based all-solid-state battery positive electrode material.
[0018] The high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material of the present invention can be prepared by mixing nickel cobalt manganese oxide particles and nickel salt and then sintering the nickel salt to decompose the nickel salt into nickel oxide, thereby forming a rock salt phase of nickel oxide on the nickel cobalt manganese oxide particles, and achieving uniform wrapping of the nickel oxide on the surface of the nickel cobalt manganese oxide particles, thereby constructing a surface stabilization layer. The process has strong production stability and can be applied to mass production of materials.
[0019] Preferably, in S2, the mixing is: stirring and mixing the lithium nickel cobalt manganese oxide particles and the nickel salt in a solvent to uniformly remove the solvent; preferably, the solvent is an organic solvent; the organic solvent is preferably a mixture of one or more of alcohols, aromatic hydrocarbons, ethers, and ketones, more preferably ethanol; the amount of the solvent added is 1g of the mixture / 10-30mL of the solvent. The removal of the solvent can be carried out by conventional means to volatilize the solvent, such as under negative pressure, flowing atmosphere, heating (preferably below 100°C), etc. The sintering is preferably carried out in a muffle furnace. The heating rate to the sintering temperature is preferably 3-10°C / min, and the sintering atmosphere is an air atmosphere. The cooling is preferably naturally cooled to room temperature with the furnace.
[0020] Preferably, the nickel salt is a salt that can be decomposed into nickel oxide after sintering. Preferably, the nickel salt is at least one of nickel nitrate and its hydrate, nickel sulfate and its hydrate, and nickel hydroxide.
[0021] Preferably, the nickel salt is added in an amount such that the weight percentage of NiO in the high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material is 1 to 5%.
[0022] Preferably, the nickel salt is nickel nitrate hexahydrate, and the nickel nitrate hexahydrate accounts for 1-5% of the total molar ratio of the mixed material.
[0023] Preferably, when the nickel salt is nickel nitrate hexahydrate, the sintering temperature is 350-750° C., and the sintering time is 3-8 hours.
[0024] More preferably, when the nickel salt is nickel nitrate hexahydrate, the sintering temperature of the mixture is 350-600°C, more preferably 500-600°C, and the sintering time is 5.5-6.5 hours. The material obtained at a temperature of 500-600°C has a higher specific capacity and better cycle performance. The inventor believes that the possible reason is that at a lower sintering temperature (about 350°C), nickel nitrate hexahydrate mainly undergoes dehydration and partial nitrate decomposition reactions, and NiO is not fully formed. At 500-600°C, nickel nitrate hexahydrate can be completely decomposed to achieve high nickelization on the surface, but at more than 700°C, NiO enters the bulk phase of the material, which will hinder the transmission of lithium ions, thereby limiting its electrochemical performance. Therefore, at 500-600°C, nickel oxide can be better evenly wrapped on the surface of nickel cobalt manganese oxide lithium particles, thereby constructing a surface stabilization layer and achieving better material performance.
[0025] Preferably, the nickel nitrate hexahydrate accounts for 2-4% of the total molar ratio of the mixed material, and more preferably 2-3%.
[0026] The present invention also aims to provide an all-solid-state battery positive electrode material, comprising: the high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material described above or the high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material prepared by the method described above.
[0027] Preferably, the all-solid-state battery positive electrode material also contains a halide solid electrolyte, a conductive additive and a binder. Further preferably, the all-solid-state battery positive electrode material includes the following components in weight percentage: 50-85% positive electrode active material, 15-50% halide solid electrolyte, and 0.5-10% conductive additive.
[0028] Preferably, the chemical formula of the halide solid electrolyte is Li 6 PS 5 Cl and / or Li a MXb , among which Li a MX b wherein M is selected from at least one of Al, Ga, In, Sc, Y and La series elements; X is selected from at least one of F, Cl and Br; 0≤a≤10; 1≤b≤13; the halide solid electrolyte is more preferably Li 6 PS 5 Cl and Li 3 InCl 6 At least one of; preferably, the conductive additive is selected from at least one of conductive carbon black, carbon nanotubes, carbon nanofibers, acetylene black, conductive graphite and graphene.
[0029] The present invention also aims to provide an all-solid-state battery, comprising the above-mentioned all-solid-state battery positive electrode material, a solid electrolyte layer and a metal negative electrode. Preferably, the metal negative electrode is selected from metal indium, metal lithium, alloy, carbon negative electrode, tin-based negative electrode or nano oxide. Preferably, the solid electrolyte is selected from one or more of halides, sulfides, oxides and polymers. Preferably, the solid electrolyte layer is a double-layer solid electrolyte, and the side close to the positive electrode is Li 3 InCl 6 Solid electrolyte layer, Li near the negative electrode 6 PS 5 Cl solid electrolyte layer.
[0030] Compared with the prior art, the present invention has the following beneficial effects: the high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material of the present invention is lithium nickel cobalt manganese oxide with a NiO layer coated on the surface. The chemical stability of the surface NiO coating layer enables it to act as a protective layer at the positive electrode / electrolyte interface. On the one hand, it can stabilize the surface lattice oxygen of the positive electrode material and reduce its phase degradation during the cycle; on the other hand, it can also serve as a buffer layer to limit the direct contact between the positive electrode material and the solid electrolyte, thereby weakening the side reaction between the positive electrode material and the solid electrolyte, thereby further improving its specific capacity and cycle stability, and improving the electrochemical properties of the material, especially when applied to all-solid-state batteries, it can improve the specific capacity and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a SEM image of the lithium nickel cobalt manganese oxide particles described in Comparative Example 1;
[0032] Figure 2 (a) is a statistical graph of the particle size distribution of the primary particles of the nickel cobalt manganese oxide particles described in Comparative Example 1, and (b) is a statistical graph of the particle size distribution of the secondary particles of the nickel cobalt manganese oxide particles described in Comparative Example 1;
[0033] Figure 3The SEM images of the high-nickel lithium-rich manganese-based all-solid-state battery positive electrode materials described in Examples 1 to 9, wherein Example 1 is (a), Example 2 is (b), Example 3 is (c), Example 4 is (d), Example 5 is (e), Example 6 is (f), Example 7 is (g), Example 8 is (h), and Example 9 is (i);
[0034] Figure 4 This is the SEM-EDS surface scanning distribution diagram of the high-nickel lithium-rich manganese-based all-solid-state battery positive electrode material described in Example 5;
[0035] Figure 5 The first charge and discharge curves of the high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode materials described in the comparative example and Example 5;
[0036] Figure 6 The cycle performance diagram of the all-solid-state battery of the modified high-nickel lithium-rich manganese-based positive electrode material described in Example 5 and the unmodified lithium-rich manganese-based positive electrode material of the comparative example;
[0037] Figure 7 (a) is a linear TEM scan of the high-nickel lithium-rich manganese-based all-solid-state battery positive electrode material described in Example 5, and (b) is a linear TEM-EDS intensity signal diagram corresponding to (a);
[0038] Figure 8 HRTEM image and FFT image of the high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material described in Example 5. DETAILED DESCRIPTION
[0039] In order to better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0040] In the following examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0041] Example 1
[0042] The present invention discloses an embodiment of a high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material. The high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material in this embodiment comprises a nickel cobalt manganese oxide lithium core and a NiO layer coated on the surface of the core; the nickel cobalt manganese oxide lithium core is a nickel cobalt manganese oxide lithium particle Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 , purchased from CLUDE, D50 (secondary particles) is 5.67 μm, the D50 particle size of primary particles is 0.46 μm, and its SEM image is shown in Figure 1 The particle size distribution statistics of primary and secondary particles are shown in Figure 2 .
[0043] The method for preparing the high-nickel lithium-rich manganese-based all-solid-state battery positive electrode material described in this embodiment comprises the following steps:
[0044] S1. Obtaining lithium nickel cobalt manganese oxide particles;
[0045] S2. Weigh nickel cobalt manganese oxide particles, weigh nickel nitrate hexahydrate at a rate of 1% of the total molar amount of nickel nitrate hexahydrate and nickel nitrate hexahydrate, add 1 g of the mixture into 20 mL of 95% ethanol solution, stir and mix evenly, dry at 80°C to obtain a mixture, place the mixture in a corundum ark, move it to a muffle furnace, heat it to 350°C at a heating rate of 5°C / min in an air atmosphere, keep it warm for 6 hours, and then naturally cool it to room temperature with the furnace to obtain the high-nickel lithium-rich manganese-based all-solid-state battery positive electrode material.
[0046] Example 2
[0047] The difference between this embodiment and embodiment 1 is that the amount of nickel nitrate hexahydrate added is different. In this embodiment, nickel nitrate hexahydrate is weighed and added so that the nickel nitrate hexahydrate accounts for 2.5% of the total molar amount of the lithium nickel cobalt manganese oxide particles and the nickel nitrate hexahydrate.
[0048] Example 3
[0049] The difference between this embodiment and embodiment 1 is that the amount of nickel nitrate hexahydrate added is different. In this embodiment, nickel nitrate hexahydrate is weighed and added at 5% of the total molar amount of the lithium nickel cobalt manganese oxide particles and the nickel nitrate hexahydrate.
[0050] Example 4
[0051] The difference between this embodiment and embodiment 1 is the sintering temperature in S2. In this embodiment, the sintering temperature is 550°C, which is recorded as LLO (550, 1%).
[0052] Example 5
[0053] The difference between this embodiment and embodiment 1 is that the amount of nickel nitrate hexahydrate added and the sintering temperature are different. In this embodiment, nickel nitrate hexahydrate is weighed and added at a rate of 2.5% of the total molar amount of lithium nickel cobalt manganese oxide particles and nickel nitrate hexahydrate, and the sintering temperature is 550°C, recorded as LLO (550, 2.5%).
[0054] Example 6
[0055] The difference between this embodiment and embodiment 1 lies in the amount of nickel nitrate hexahydrate added and the sintering temperature. In this embodiment, nickel nitrate hexahydrate is weighed and added at 5% of the total molar amount of lithium nickel cobalt manganese oxide particles and nickel nitrate hexahydrate, and the sintering temperature is 550°C, recorded as LLO (550,5%).
[0056] Example 7
[0057] The difference between this embodiment and embodiment 1 is the sintering temperature in S2. In this embodiment, the sintering temperature is 750°C.
[0058] Example 8
[0059] The difference between this embodiment and embodiment 1 is that the amount of nickel nitrate hexahydrate added and the sintering temperature are different. In this embodiment, nickel nitrate hexahydrate is weighed and added at a rate of 2.5% of the total molar amount of lithium nickel cobalt manganese oxide particles and nickel nitrate hexahydrate, and the sintering temperature is 750°C.
[0060] Example 9
[0061] The difference between this embodiment and embodiment 1 is that the amount of nickel nitrate hexahydrate added and the sintering temperature are different. In this embodiment, nickel nitrate hexahydrate is weighed and added at 5% of the total molar amount of lithium nickel cobalt manganese oxide particles and nickel nitrate hexahydrate, and the sintering temperature is 750°C.
[0062] Comparative Example
[0063] This comparative example is the lithium nickel manganese oxide particles Li in Example 1 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 , denoted as LLO.
[0064] Effect example
[0065] Preparation of all-solid-state battery positive electrode material: The high-nickel lithium-rich manganese-based all-solid-state battery positive electrode material and the electrolyte Li 3 InCl 6 The conductive additive C65 is mixed in a weight ratio of 66.5:28.5:5 to obtain a positive electrode material.
[0066] Assembly of all-solid-state batteries: Take 55mg Li 6 PS 5 Cl was placed in a pressure mold (10 mm in diameter) and compacted under 1 ton of pressure, and 55 mg Li was added to the upper layer. 3 InCl 6 , compressed under the same 1 ton pressure, and then 3 InCl 610 mg of all-solid-state battery positive electrode material was added above the electrolyte and maintained at 3 tons pressure for 2 minutes. 6 PS 5 A high-purity indium sheet (thickness 0.1 mm), a lithium sheet (0.05 mm) and a copper sheet (0.008 mm) are placed on one side of the Cl electrolyte sheet in sequence and put into the battery mold to complete the assembly of the all-solid-state battery.
[0067] The assembled all-solid-state battery was tested for performance using a charge and discharge tester at an ambient temperature of 25°C and an operating voltage range of 1.4 to 4.2V. The battery was first activated three times at a current of 0.1C.
[0068] The test results are shown in Table 1.
[0069] Table 1
[0070]
[0071]
[0072] It can be seen from the results in Table 1 that nickel nitrate hexahydrate is added to the nickel manganese oxide material according to the nickel nitrate hexahydrate accounting for 1-5% of the total molar amount of nickel cobalt manganese oxide particles and nickel nitrate hexahydrate. The discharge performance and capacity retention rate of the positive electrode material with a NiO weight percentage of 1-5% formed after sintering are better than those of the nickel manganese oxide material without NiO coating, and the discharge performance can reach more than 140mAh / g under the first cycle (0.1C), and the capacity retention rate after 300 cycles can be more than 53%. Especially when the sintering temperature is 550°C and the nickel nitrate hexahydrate accounts for 2.5% of the total molar amount of nickel cobalt manganese oxide particles and nickel nitrate hexahydrate, Example 5 is the best in the first discharge performance and the capacity retention rate after 300 cycles. Below 750°C, as the temperature increases, the surface nickel-rich treatment can improve the discharge performance of the lithium-rich manganese-based positive electrode material. At the same temperature, the capacity retention rate increases first and then decreases with the increase of the coating amount. Especially when the sintering temperature is 550°C and the nickel nitrate hexahydrate accounts for 2.5% of the total molar amount of the lithium nickel cobalt manganese oxide particles and nickel nitrate hexahydrate (that is, the theoretical weight percentage of NiO in the high-nickel-rich lithium manganese-based all-solid-state battery positive electrode material is about 2.77%), the performance improvement effect is most significant. This shows that the surface nickel-rich treatment can improve the specific capacity and cycle performance of the material.
[0073] from Figure 3 It can be seen that the surfaces of all the example materials have no obvious changes and still maintain the morphology of the comparative example samples. The high nickel content of the surface does not change its morphology.
[0074] Figure 4This is the SEM-EDS surface scanning distribution diagram and EDS surface scanning component distribution diagram of the high-nickel-rich lithium-manganese-based all-solid-state battery positive electrode material described in Example 5. It can be seen from the figure that the Ni element is evenly distributed in the material, the surface coating layer has a high uniformity, and no obvious segregation occurs.
[0075] from Figure 5 It can be seen that the first discharge performance of the positive electrode material coated with rock salt phase nickel oxide is better than that of the uncoated control example.
[0076] from Figure 6 It can be seen that compared with the uncoated control example, the positive electrode material coated with rock salt phase nickel oxide has better specific capacity and cycle performance.
[0077] from Figure 7 It can be seen that the Ni content on the surface of the sample with high nickel content is higher than that in the bulk phase, which further proves the existence of the surface NiO coating.
[0078] from Figure 8 It can be seen that there is an obvious NiO layer on the surface of the material, while the bulk phase still maintains a typical layered structure.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material, characterized in that: It comprises a lithium nickel cobalt manganese oxide core and a NiO layer coated on the surface of the core; The chemical formula of the lithium nickel cobalt manganese oxide core is shown in formula (I): aLi2MnO3·(1-a)LiMn 1 / 3 Ni 1 / 3 Co 1 / 3 O2(I) Where 0.4<a<0.6; In the high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material, the weight percentage of NiO is 1-5%.
2. The high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material according to claim 1, characterized in that: The lithium nickel cobalt manganese oxide core is a spherical particle with a D50 of 1 to 10 μm, and the thickness of the NiO layer is 5 to 20 nm.
3. The high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material according to claim 1, characterized in that: The average particle size of the lithium nickel manganese cobalt oxide core is 3 to 7 μm.
4. The high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material according to claim 1, characterized in that: In the high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material, the weight percentage of NiO is 2-4%.
5. The method for preparing the high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Obtaining lithium nickel cobalt manganese oxide particles; S2. Evenly mix the nickel cobalt manganese oxide particles and the nickel salt to obtain a mixture, sinter the mixture to decompose the nickel salt into nickel oxide, and cool the mixture to obtain the high-nickel lithium-rich manganese-based all-solid-state battery positive electrode material.
6. The method for preparing the high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material according to claim 5, characterized in that: The nickel salt is at least one of nickel nitrate and its hydrate, nickel sulfate and its hydrate, and nickel hydroxide.
7. The method for preparing the high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material according to claim 6, characterized in that: The nickel salt is nickel nitrate hexahydrate, and the nickel nitrate hexahydrate accounts for 1-5% of the total molar ratio of the mixed material.
8. The method for preparing the high-nickel, lithium-rich manganese-based all-solid-state battery positive electrode material according to claim 7, characterized in that: The sintering temperature is 350-750° C., and the sintering time is 3-8 hours.
9. An all-solid-state battery positive electrode material, characterized in that: It comprises: the high-nickel-rich-lithium-manganese-based all-solid-state battery positive electrode material as described in any one of claims 1 to 4 or the high-nickel-rich-lithium-manganese-based all-solid-state battery positive electrode material prepared by the method as described in any one of claims 5 to 8.
10. An all-solid-state battery, characterized in that: It comprises the all-solid-state battery positive electrode material, a solid electrolyte layer and a metal negative electrode as described in claim 9.
Citation Information
Patent Citations
Method for preparing lithium-enriched manganese-based anode material of nano-oxide-coated lithium ion battery
CN103441252A
Non-aqueous electrolyte secondary battery and positive electrode active material for use in same
CN105703011A
Preparation method and application of magnesium aluminate-coated lithium-rich manganese-based positive electrode material
CN113991097A
Lithium-rich manganese-based positive electrode material with low voltage drop and high cycle stability, preparation method and lithium ion lithium battery
CN117117169A
Cited By
Modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
CN121964604A
A modified lithium-rich manganese-based positive electrode material, a preparation method and application thereof
CN121964604B
Cathode active material for lithium secondary battery, method of preparing the same and lithium secondary battery including the same
KR103000540B1